STRATEGI PENGEMBANGAN USAHA PENGRAJIN TAHU MESA JAYA KOTA BEKASI: BUSINESS DEVELOPMENT STRATEGY OF TOFU "MESA JAYA" IN BEKASI CITY - Nursinah, Is Zunaini; Ismarani, Ismarani; Syaputra, Olga (CEFARS : JURNAL AGRIBISNIS DAN PENGEMBANGAN WILAYAH, 2023)
The Mesa Jaya tofu business is one of the tofu producers in Bantar Gebang District, Bekasi City. This research aims to identify internal factors (strengths and weaknesses), and identify external factors (opportunities and threats) and formulate alternative business development strategies. The method used in this research is a case study with a qualitative descriptive approach, data analysis consists of qualitative and quantitative methods, for qualitative analysis using descriptive and observational methods to describe the process of business activities and determine alternative development strategies, while for quantitative analysis using tools in the form of IFE Matrix, EFE Matrix and SWOT Matrix and QSPM Matrix. The results of this Mesa Jaya tofu business research are in cell 1 automatically entered into quadrant 1 (grow and build strategy). This position will find a development strategy that can be implemented by the company, the strategy that should be implemented by the Mesa Jaya tofu business is grow and build or a strategy of growing and building. This strategy is in line with the SO strategy, which is to expand marketing reach inside and outside Bantar Gebang District, the WO strategy increases innovation by utilizing a large number of tofu enthusiasts, and the WT strategy improves business management so that it can compete well.